2014
DOI: 10.1016/j.jchf.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Risk Across the Spectrum of Ankle-Brachial Index

Abstract: Objectives To describe the relationship between ankle brachial index (ABI) and the risk for heart failure (HF). Background The ABI is a simple, non-invasive measure associated with atherosclerotic cardiovascular disease and death; however, the relationship between ABI and risk of HF is less well characterized. Methods Between 1987–1989 in the Atherosclerosis Risk in Communities study an oscillometric device was used to measure blood pressure in a single upper and randomly chosen lower extremity to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 50 publications
4
24
0
1
Order By: Relevance
“…In a community cohort of middle aged Americans, it was found that a low ABI was associated with a 40% higher risk of heart failure than a normal ABI, and a borderline ABI was also associated with an increased risk of heart failure [20]. Similarly, in the present study, we found that low and borderline ABIs were strongly associated with future heart failure in hospitalized cardiology patients.…”
Section: Discussionsupporting
confidence: 83%
“…In a community cohort of middle aged Americans, it was found that a low ABI was associated with a 40% higher risk of heart failure than a normal ABI, and a borderline ABI was also associated with an increased risk of heart failure [20]. Similarly, in the present study, we found that low and borderline ABIs were strongly associated with future heart failure in hospitalized cardiology patients.…”
Section: Discussionsupporting
confidence: 83%
“…Our study demonstrates future diabetes as another adverse clinical consequence of PAD in addition to its known complications such as other cardiovascular diseases and impaired functional status [3, 4, 7, 26, 4044]. This finding is important given the adverse outcomes associated with diabetes [4449].…”
Section: Discussionmentioning
confidence: 56%
“…However, the independent associations of lower ABI with lower grip strength suggest the involvement of systemic pathophysiology. Low ABI is an indicator of systemic atherosclerosis and thus, those with low ABI often have other manifestations of cardiovascular disease such as stroke and heart failure, 36 which may lead to poor systemic physical function. However, of note, the association of ABI with physical function was independent of other cardiovascular subtypes.…”
Section: Discussionmentioning
confidence: 99%